The Influence of Environmental Corporate Social Responsibility (ECSR), Green Supply Chain Management (GSCM), And Supply Chain Digitalization (SCD) on Green Competitiveness Through the Mediation of Top Management Commitment in MSMES in Indonesia - Fajar, Achmarul; Tirta Firdaus, Sukma Umbara; Fatimah, Putri Umbara; Megarani, Ayunida Retno; Afriliana, Diana Retno (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study investigates the impact of Environmental Corporate Social Responsibility (ECSR), Green Supply Chain Management (GSCM), and Supply Chain Digitalization (SCD) on Green Competitiveness (GCA), with Top Management Commitment (TMC) as a mediating variable, in the context of MSMEs in Indonesia. A quantitative research approach is employed, using a structured questionnaire distributed to 490 MSME managers in the districts of Pamekasan and Sampang. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through WarpPls software to explore direct, indirect, and mediating relationships between the variables. The findings show that ECSR, GSCM, and SCD significantly influence GCA, with TMC acting as a significant mediator that strengthens these relationships. Additionally, the results highlight the critical role of TMC in facilitating the successful integration of environmental and digital supply chain practices in enhancing green competitiveness. This study contributes to the body of knowledge by integrating ECSR, GSCM, and SCD with TMC in a comprehensive model that addresses the research gap in understanding the synergy between these practices in MSMEs. The study provides practical insights for MSMEs on how to strategically align environmental practices and digital transformation to enhance competitiveness. Future research should explore additional variables such as organizational culture or external market factors